Proceedings of the 2005 Particle Accelerator Conference
DOI: 10.1109/pac.2005.1591465
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Low Loss SRF Cavity for the ILC

Abstract: An international team comprising SLAC, KEK, FNAL, JLAB and DESY is collaborating on the design, fabrication and test of a low loss, 1.3 GHz 9-cell SRF structure as a potential improvement for the ILC main linac. The advantages of this structure over the TESLA structure include lower cryogenic loss, shorter rise time, and less stored energy. Among the issues to be addressed in this design are HOM damping, Lorentz force detuning and multipacting. We will report on HOM damping calculations using the parallel fini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…Table II lists characteristics of three cavity shapes currently being investigated and Fig. 3 shows their cross sections [9]- [11].…”
Section: A Cavity Shapesmentioning
confidence: 99%
“…Table II lists characteristics of three cavity shapes currently being investigated and Fig. 3 shows their cross sections [9]- [11].…”
Section: A Cavity Shapesmentioning
confidence: 99%
“…The larger end-pipe radius has a significant impact on the third band damping as well as the FM coupling. The required external Q ext for a matched FM coupling for a beam current of 11.8 mA and a gradient of 40 MV/m is about 3.4x10 6 . To obtain such a Qext for the FM mode, the end-pipe radius was initially assumed to be 41 mm to avoid deep intrusion of the center conductor of the FM coupler into the beam pipe.…”
Section: End Group Design Considerationmentioning
confidence: 99%
“…Preliminary studies of the proposed LL cavity have shown unacceptable damping factors [6] for the high R/Q modes in the 3 rd dipole band if the typical TESLA HOM couplers are directly adapted to the design. In the high gradient tests of the 9-cell prototype ICHIRO cavity at KEK, strong multipacting barriers were observed at around 30-MV/m although a single LL cell had achieved a higher gradient.…”
Section: Introductionmentioning
confidence: 99%
“…Note that in this convention, if the wall angle is greater than 90 0 , the cavity geometry is called the re-entrant geometry. Generally, there is a constraint on the maximum value of the wall angle , which is decided by the mechanical considerations, ease of chemical cleaning [12], etc. In our optimization studies, we have explored the case when there is no such constraint on , and found that the performance is improved for higher values .…”
Section: Introductionmentioning
confidence: 99%